Multiple knowledge of network diversity: intercultural connections in the debate over digital inclusion with respect of the people of the forest - Moura, Ricardo Damasceno (Revista Brasileira de Pós-Graduação, 2014)
The article analyzes digital inclusion in the Amazon, focusing on the reasons for digital/intercultural inclusion; multiple existing cultural knowledge; the implementation of new information technologies and knowledge, taking into account ethnology in cyber culture. Additionally, it seeks to understand this new digital inclusion based on the realinterests of the peoples and traditional populations of the Amazon. It emphasizes the digital inclusion proposals present on the Government agenda, in order to question the difficult access by riparian, indigenous and Quilombola (descendents from Afro-Brazilian slaves) populations, considering that public policies for digital inclusion do not reach these populations. With this study in essayistic nature, we have come to the conclusion that there is still much to be done for the traditional peoples of the Amazon, starting by recognizing their cultures and the achievement of citizenship.